Epidemiological and Clinical Profile of Dermatoses Observed in Chronic Hemodialysis Patients at the National Teaching Hospital (NTH-HKM) of Cotonou, Benin - Hugues Adégbidi; Fabrice Akpadjan; Odile Houngbo; Jacques Vigan; Bérénice Dégboé; Nadège Agbessi; Christiane Koudoukpo; Félix Atadokpèdé (Dermatology Research and Practice)
Introduction. Dermatological damage in chronic hemodialysis patients is not uncommon. In Benin, to date, no study on the dermatological manifestations of chronic hemodialysis patients has been carried out. However, the presence of cutaneous signs is evident in these patients, and the need for dermatological care is not negligible. The objective of this study was to identify the epidemiological and clinical profile of the main dermatological manifestations presented by chronic hemodialysis patients at the NTH-HKM of Cotonou (Benin). Methods. This was a descriptive cross-sectional study conducted in chronic hemodialysis patients from May 15th to September 15th, 2018. Included were all patients seen during the study period who had been on hemodialysis for at least three months, had at least one dermatological manifestation, and gave verbal or written consent. Chronic hemodialysis patients who did not wish to participate in the survey were excluded. Results. 87 patients were included in the study for a hospital frequency of 33.8%. The sex ratio (male to female) was 2. The median age was 49 years (IQ [40.75–59]). Median age in hemodialysis was 36 months with two weekly sessions. The main dermatological manifestations were xerosis (48.3%), pruritus (34.5%), alopecia (14%), nail dystrophy (9.2%), equisegmented nails (8%), and melanoderma (8%). Pruritus was associated with a longer duration of hemodialysis sessions p=0.01, while xerosis, alopecia, and melanoderma were associated with seniority in hemodialysis. Conclusion. Cutaneous manifestations in hemodialysis patients were frequent and dominated by xerosis, pruritus, and alopecia. Factors associated with some of these dermatologic manifestations were seniority in hemodialysis, long duration of the hemodialysis session, and female gender.